Therapeutic Applications of Human and Bovine Colostrum in the Treatment of Gastrointestinal Diseases and Distinctive Cancer Types: The Current Evidence - Siddhi Bagwe-Parab; Pratik Yadav; Ginpreet Kaur; Hardeep Singh Tuli; Harpal Singh Buttar (Frontiers Media S.A., 2020)
The incidence of gastrointestinal disorders (GID) and cancers is escalating all over the world. Limited consumption of colostrum by newborns not only weakens the immune system but also predisposes infants to microbial infections. Colostrum is nature's perfect food, sometimes referred to as the 'elixir of life'. Breast-fed infants have a lower incidence of GI tract infections than infants fed formula or cow's milk. As per WHO statistics, cancer is the most prevalent disease globally and causes 9.6 million deaths worldwide. The current strategies for treating cancer include chemotherapy, radiation, and surgery. However, chemotherapy and radiation exposure are usually associated with serious long-term side effects and deterioration in the quality of life (QOL) of patients. Furthermore, the hospitalization and medication costs for treating cancers are exorbitant and impose high economic burden on healthcare systems. People are desperately looking for cost-effective and affordable alternative therapies for treating GID and cancers. Therefore, there is an urgent need for clinically evaluating the anticancer compounds isolated from plants and animals. Such therapies would not only be economical and have fewer side effects, but also help to improve the QOL of cancer patients. Recently, bovine colostrum (BC) has caught the attention of many investigators to explore its anticancer potential in humans. BC impregnated dressings are highly effective in treating chronic wounds and diabetic foot ulcer. BC is rich in lactoferrin, a glycoprotein with strong antioxidant, anti-inflammatory, anti-cancer, and anti-microbial properties. Intravaginal application of BC tablets is effective in causing the regression of low-grade cervical intraepithelial neoplasia. The underlying mechanisms of BC at cellular, genetic, and molecular levels remain to be ascertained. Oral BC supplement is well-tolerated, but some people may experience problems such as flatulence and nausea. Well-designed, randomized, placebo-controlled, clinical trials are needed to access the therapeutic potential, long-term safety, and optimal doses of BC products. This review is aimed to highlight the anticancer potential of BC and its components, and the therapeutic applications of BC supplements in treating gastrointestinal diseases in children and adults. We also discuss the health promotion benefits and therapeutic potential of BC nutraceuticals in reducing the incidence of non-communicable diseases.